Governing the world the history of an idea - Mazower, Mark (Allen Lane, 2012)
In 1815 the shocked and exhausted victors of the decades of fighting that had engulfed Europe for a generation agreed to a new system for keeping the peace. This title tells the history of two centuries of international government that also goes to the heart of current world crises.